Recognition and Learning of Emotions by Primary School Children on the Autism Spectrum: A Study Using Tablets - Syriopoulou, Christine; Hatzigiannakoglou, Paul; Liaratsika, Konstantina (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Autism Spectrum Disorder is a neurodevelopmental disorder that affects, among other things, the emotional intelligence of children with autism. The purpose of this study is to investigate the recognition and acquisition of emotional knowledge by elementary school children with autism through the use of a tablet-based game. Additional objectives include assessing the difference in emotional recognition responses between children with autism and children with emotional difficulties, as well as evaluating the ability to associate each emotion with the corresponding facial expression. The study also aimed to examine the amount of time a student can remain focused without displaying stereotypical behaviors, and how long it takes for a student to respond to a command. In this study, 22 students from Creative Activity Centers and speech therapy centers in mountainous northern part of the country, participated by playing a tablet game. Among them, 6 were children with autism, 6 had emotional difficulties, and 10 were typically developing children. Data were analyzed using the method of systematic observation and recording. The results showed that children with autism exhibited stereotypical behaviors during the game up to 75%, responded more quickly than the children with emotional difficulties, sought visual contact with the supervisor and the Panda game, and had the lowest rate of correctly matching each emotion with the corresponding emoticon.